Conference equity in global health: a systematic review of factors impacting LMIC representation at global health conferences - Samantha Ann Johnson; Paul Truche; Lotta Velin; Jean-Wilguens Lartigue; Anudari Zorigtbaatar; Ulrick Sidney Kanmounye; Michelle Nyah Joseph (BMJ Global Health)
Introduction Global health conferences are important platforms for knowledge exchange, decision-making and personal and professional growth for attendees. Neocolonial patterns in global health at large and recent opinion reports indicate that stakeholders from low- and middle-income countries (LMICs) may be under-represented at such conferences. This study aims to describe the factors that impact LMIC representation at global health conferences.Methods A systematic review of articles reporting factors determining global health conference attendance was performed using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Articles presenting conference demographics and data on the barriers and/or facilitators to attendance were included. Articles were screened at title and abstract level by four independent reviewers. Eligible articles were read in full text, analysed and evaluated with a risk of bias assessment.Results Among 8765 articles screened, 46 articles met inclusion criteria. Thematic analysis yielded two themes: ‘barriers to conference attendance’ and ‘facilitators to conference attendance’. In total, 112 conferences with 254 601 attendees were described, of which 4% of the conferences were hosted in low-income countries. Of the 98 302 conference attendees, for whom affiliation was disclosed, 38 167 (39%) were from LMICs.Conclusion ‘Conference inequity’ is common in global health, with LMIC attendees under-represented at global health conferences. LMIC attendance is limited by systemic barriers including high travel costs, visa restrictions and lower acceptance rates for research presentations. This may be mitigated by relocating conferences to visa-friendly countries, providing travel scholarships and developing mentorship programmes to enable LMIC researchers to participate in global conferences.